Rapid Growth of Large Forest Fires Drives the Exponential Response of Annual Forest‐Fire Area to Aridity in the Western United States. Issue 5 (8th March 2022) - Juang, C. S.; Williams, A. P.; Abatzoglou, J. T.; Balch, J. K.; Hurteau, M. D.; Moritz, M. A.
Abstract: Annual forest area burned (AFAB) in the western United States (US) has increased as a positive exponential function of rising aridity in recent decades. This non‐linear response has important implications for AFAB in a changing climate, yet the cause of the exponential AFAB‐aridity relationship has not been given rigorous attention. We investigated the exponential AFAB‐aridity relationship in western US forests using a new 1984–2019 database of fire events and 2001–2020 satellite‐based records of daily fire growth. While forest‐fire frequency and duration grow linearly with aridity, the exponential AFAB‐aridity relationship results from the exponential growth rates of individual fires. Larger fires generally have more potential for growth due to more extensive firelines. Thus, forces that promote fire growth, such as aridification, have more potent effects on larger fires. As aridity increases linearly, the potential for growth of large fires accelerates, leading to exponential increases in AFAB. Plain Language Summary: Though a natural phenomenon in the western United States (US), wildfires have burned over increasingly large forested areas as the climate has warmed and dried in recent decades, straining fire management and putting humans at risk. An important characteristic of the wildfire response to climate is that as fuels dry–mainly from low precipitation and heat–the amount of annual forest area burned increases exponentially. Although scientists frequently use this relationship to project wildfire responses to climate change, the cause of the exponential relationship has not been robustly investigated. We show here that the exponential response of annual burned area to fuel dryness is related to how individual wildfires spread. Fire growth is a dispersion phenomenon–similar to how the area of a circle increases exponentially as the radius grows incrementally, wildfires tend to grow at compounding rates; the larger a fire, the more potential it has for rapid growth. As western US forest fires have grown under climate change, larger fires have grown more rapidly than smaller fires and increases in annual forest‐fire area have therefore accelerated. Annual western US forest area burned will likely continue to increase due to warming and drying until fuel availability becomes a limiting factor. Key Points: We developed a database of western United States wildfires and examined why annual forest area burned grows exponentially with aridity Individual fires grow at compounding rates, so fire enlargement driven by aridification is most rapid among large fires Approximately two‐thirds of the increase in 1984–2019 forest burned area is shaped by each year's largest 10% of forest fires